2014
DOI: 10.1002/hep.27328
|View full text |Cite
|
Sign up to set email alerts
|

IL‐34 and macrophage colony‐stimulating factor are overexpressed in hepatitis C virus fibrosis and induce profibrotic macrophages that promote collagen synthesis by hepatic stellate cells

Abstract: Chronic hepatitis C virus (HCV) infection is characterized by progressive hepatic fibrosis, a process dependent on monocyte recruitment and accumulation into the liver. The mediators expressed in chronically injured liver that control the differentiation of human monocytes into profibrotic macrophages (Mu) remain poorly defined. We report that chronically HCV-infected patients with high fibrosis stages have higher serum levels of macrophage colony-stimulating factor (M-CSF) and interleukin (IL)234 than HCV-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 42 publications
5
126
1
Order By: Relevance
“…Hemozoin activates macrophages by stimulating inflammatory signaling pathways, including Toll-like receptor 4 activation and NF-kB signaling. The activated macrophages produce inflammatory cytokines, such as IL1b and TNF-a, which accelerate HSC activation, contributing to liver fibrosis [32,46,[55][56][57][58]. In the present study, we found that Kupffer cell activation, hemozoin accumulation, and upregulation of pro-inflammatory genes were apparent in malaria-infected livers (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Hemozoin activates macrophages by stimulating inflammatory signaling pathways, including Toll-like receptor 4 activation and NF-kB signaling. The activated macrophages produce inflammatory cytokines, such as IL1b and TNF-a, which accelerate HSC activation, contributing to liver fibrosis [32,46,[55][56][57][58]. In the present study, we found that Kupffer cell activation, hemozoin accumulation, and upregulation of pro-inflammatory genes were apparent in malaria-infected livers (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, other research groups reported that M-CSF was associated with hepatic fibrosis in chronic hepatitis C and non-alcoholic fatty liver disease patients3132. Moreover, they found that M-CSF could be produced from hepatocytes with persistent HCV infection31. In this study, there was a significant difference in the percentages of PD-L1 + MDSCs between patients with HCC and those with chronic hepatitis.…”
Section: Discussionmentioning
confidence: 41%
“…They demonstrated that the increase in MDSCs was only correlated with tumor progression, but not with hepatic fibrosis or the disease activity of chronic liver disease30. On the other hand, other research groups reported that M-CSF was associated with hepatic fibrosis in chronic hepatitis C and non-alcoholic fatty liver disease patients3132. Moreover, they found that M-CSF could be produced from hepatocytes with persistent HCV infection31.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the already identified functions of IL-34 and M-CSF in exacerbated macrophage activation (bowel diseases, liver fibrosis, chronic skin inflammation, arthritis, etc. ), this new heteromeric cytokine M-CSF/IL-34 which may differentially regulates the activation/localization of M-CSFR strengthens the global therapeutic approaches for blocking all biological functions coming from these molecules [7,8,[45][46][47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 91%